Research Advances in the Treatment of Urinary System Diseases with “Zhibian”(BL54)-toward-“Shuidao” (ST28) - Jia, Yan’e; Tang, Yuanshan (Journal of Contemporary Medical Practice, 2025)
The needling technique of directionally penetrating from “Zhibian” (BL54)-toward-“Shuidao” (ST28) is a characteristic long-needle deep-penetration method in Traditional Chinese Medicine (TCM), originating from *Huangdi Neijing* (Yellow Emperor’s Inner Canon). It demonstrates significant efficacy and broad application potential in treating genitourinary disorders. This paper systematically reviews the technique’s historical origins, anatomical foundations, and standardized protocols. Clinical evidence supporting its therapeutic advantages—such as bidirectional bladder function modulation, alleviation of prostatic diseases, and management of stress urinary incontinence—is critically analyzed. Mechanistically, the role of apoptotic factor regulation and neuroendocrine network modulation is explored. Current research has established a standardized technical framework. Future studies should expand evidence-based investigations into its application for perimenopausal syndrome and ovarian hyporesponse.